BEYOND ARISTOCRATIC STRATEGIES: POPULAR AND SUBALTERN EXPERIENCES IN SIDONIUS’ LETTERS (430–486 AD) (Alétheia - Estudos sobre Antiguidade e Medievo, 2024)
Sidonius Apollinaris (c. 430–486) letter collection constitutes an essential corpus for understanding the transformations that Gaul underwent as Roman rule retreated and other political entities took its place. The 146 letters addressed to 117 powerful and influential individuals allow us to learn about the strategies adopted by the elite to maintain their social privileges in a political scenario that much differed from that of the previous century. The epistolary exchange was part of a series of obligations aimed at maintaining bonds of friendship in an aristocratic world, but the daily life from which these messages emerged was a field permeated by the experiences of other social groups in such a way that the experiences of the non-elite, although rarely approached by scholars, could not be absent from the content of these letters. In this study, we will seek to understand, through certain case analysis in Sidonius' letters, how subaltern and popular groups experienced and dealt with the transformations of 5th century Gaul. We argue that new opportunities for agency arose, but their vulnerable situation exposed them to other instances of violence, and new and more rigid forms of control over these groups were put in place by the aristocracy.